(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: The prevalence of KEK is high in pregnant women, and identification of the level of macronutrient adequacy in pregnant women has not yet been maximized because several KEK incidents are related to food in terms of energy, carbohydrates, protein and fat. Objective: To identify the level of adequacy of macronutrient consumption in pregnant women with chronic energy deficiency at the Giri Mulya Community Health Center Method: This research is a descriptive study, with a population of pregnant women who experience chronic energy deficiency. The total sample used was 30 people. Data were analyzed using univariate analysis. Results: The results showed that pregnant women’s energy intake was 63.3% in the Moderate deficit, Category intake was 56.7% in the Normal category, protein intake was 76.7% in the severe deficit and fat intake was 36.7% in the normal category. Conclusion: Protein intake of pregnant women who experience KEK is in the severe deficit category, energy intake is in the moderate deficit category, but carbohydrates and fat are in the normal category.